The Relationship Between Principal Management Effectiveness and Teacher Performance in Junior High Schools in the Jepara Region - Nabila, Agnesia Permata; Lani, Putri Mei; Safitri, Niken Larasati; Utamie, Zoeraia Fathia; Adhittana, Brian Wahyu (Jurnal Inovasi Pembelajaran Karakter, 2024)
Law No. 22/1999 on Regional Government brought about fundamental changes in the Indonesian education system, particularly in the aspects of management and decentralization. Although this law provides freedom and autonomy in teaching practices, schools are still obliged to comply with the requirements that have been set. The government responded to these changes with various strategies, particularly improving teacher qualifications through training programs and equalizing opportunities. Teacher qualifications at the primary, junior secondary and senior secondary school levels were adjusted in line with the new regulations. A quantitative study involving 250 teachers and principals was conducted to examine the implementation of these changes. The results are expected to serve as a reference in efforts to improve the quality of education, not only in Jepara district but also in other areas with similar characteristics. This research has deep significance in the development of education governance and the overall improvement of education quality in Indonesia..